2021
DOI: 10.3389/fmolb.2021.675437
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Ameliorates Bleomycin-Induced Pulmonary Fibrosis in Mice

Abstract: The prevalence of pulmonary fibrosis is increasing with an aging population and its burden is likely to increase following COVID-19, with large financial and medical implications. As approved therapies in pulmonary fibrosis only slow disease progression, there is a significant unmet medical need. Hyperbaric oxygen (HBO) is the inhaling of pure oxygen, under the pressure of greater than one atmosphere absolute, and it has been reported to improve pulmonary function in patients with pulmonary fibrosis. Our recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…HBO alleviates hypoxia in multiple conditions, including the hypoxemia caused by COVID-19 infection, 49 solid tumors, 50 , 51 , 52 and focal cerebral ischemia model. 53 In our previous study, we provided evidence that HBO treatment reduces HIF-1α levels in lung fibroblast induced by TGF-β, 5 supports the role of HBO in reversing hypoxia. It was reported that HBO ameliorates the EMT phenomenon in keloid tissue, 54 induces mesenchymal-to-epithelial transition in a dimethyl-alpha-benzantracene mammary rat adenocarcinoma model revealed by gene expression profiling, 55 and represses EMT and Warburg effect in hypoxic non-small cell lung cancer cells.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…HBO alleviates hypoxia in multiple conditions, including the hypoxemia caused by COVID-19 infection, 49 solid tumors, 50 , 51 , 52 and focal cerebral ischemia model. 53 In our previous study, we provided evidence that HBO treatment reduces HIF-1α levels in lung fibroblast induced by TGF-β, 5 supports the role of HBO in reversing hypoxia. It was reported that HBO ameliorates the EMT phenomenon in keloid tissue, 54 induces mesenchymal-to-epithelial transition in a dimethyl-alpha-benzantracene mammary rat adenocarcinoma model revealed by gene expression profiling, 55 and represses EMT and Warburg effect in hypoxic non-small cell lung cancer cells.…”
Section: Discussionsupporting
confidence: 56%
“…4 A, B). 5 To determine the underlying molecular mechanism, we characterized the global transcriptomic changes in bleomycin-challenged mice lungs exposed to HBO by performing RNA-Seq. Genes with a P value less than 0.05 and fold change above 1.5 were considered as DEGs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, when HBO 2 treatment is administered in hypoxic conditions with a derivational elevated HIF-1α, HBO 2 treatment decreased the disease-mediated high levels of HIF-1α [ 61 , 119 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. The evaluation of studies performed in conditions of relative hypoxia secondary to inflammation indicates that the effect of HBO 2 on HIF-1α protein expression is dependent on the number of HBO 2 sessions administered, with HBO 2 having an increasing effect when administered in up to five sessions [ 140 , 141 , 142 , 143 ], and treatment with more than six sessions having a decreasing effect under these conditions [ 47 , 120 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. However, six study results were not supportive of this trend [ 117 , 140 , 141 , 157 , 158 , 159 ].…”
Section: Tolerance To Infectionmentioning
confidence: 99%